Scenario Planning for Strategic Decision-Making in Iran\'s Health Transformation - Amin Sedaghat; Yousef Ahmadi; Ali Yaghoubipour (Iranian South Medical Journal)
Background: The Health Transformation Plan (HTP) is a comprehensive program aimed at improving Iran's healthcare system, with objectives including enhanced service accessibility, reduced treatment costs, improved service quality, and the realization of health equity. However, achieving these goals requires fundamental revisions in economic, structural, and social dimensions, adopting a future-oriented approach. This study was conducted to foresight the HTP for optimal policymaking. Materials and Methods: The research employed a mixed-methods approach, based on literature review, cross-impact analysis, and scenario development. Data were analyzed using MICMAC and Scenario Wizard software, along with expert opinions from healthcare professionals. Results: Scenario Wizard analysis identified nine highly probable scenarios out of 306, with four being the most robust. The first scenario, with an impact score of 221, was the strongest but represented an unfavorable situation where all driving forces were in crisis. The second, third, and fourth scenarios followed with scores of 181, 102, and 65, respectively. However, realizing these scenarios without fundamental economic, structural, and social reforms would not yield desirable outcomes. Conclusion: The findings revealed that financial challenges, infrastructure deficits, and misalignment between expertise and healthcare reforms are major barriers to the plan’s success. Recommendations include strengthening IT infrastructure, formulating sustainable financial policies, implementing public awareness programs, and applying futures studies methodologies. Additionally, a step-by-step, goal-oriented project management approach can enhance the plan’s effectiveness.